The Dynamic Role of Interest Rate on the Performance of the Nigerian Economy - Omotayo , Akinpelumi, F.; Tunde , Monogbe G.; Nduka , Joseph A. (African Journal of Education,Science and Technology (AJEST), 2017)
Utilizing existent literature as to the subject matter, this research appraised the influx of interest rate volatility on the performance of the Nigerian economy over a period of 1986 to 2014, using auxiliary information followed from the factual report of the Apex Nigerian bank, and using strategies, and utilizing techniques such as Unit root test, Generalized autoregressive conditional heteroscedasticity (GARCH), Impulse-Response Output and Variance-Decomposition Test to evaluate variables such as Interest rate, inflation rate, exchange rate against a sole indicator of economic performance I.e. Gross Domestic Product, it was discovered that despite the short run influx of the spill over volatility of Interest rate and inflation rate, there exist no long run volatility influence of interest rate on economic performance in Nigeria. It was thusly prescribed that the pinnacle money related establishment and applicable strategy creators ought to guarantee a loan fee framework and status that could empower development or generation and the country ought to try to use her interest rate in controlling its yield level as it rouses Gross Domestic Product.